Tunable single wavelength erbium-doped fiber ring laser based on in-line Mach-Zehnder strain - Jaddoa, M.F.; Razak, M.Z.A.; Salim, M.A.M.; Sharbirin, A.S.; Nayan, N.; Ismail, Mohammad Faizal; Ahmad, Harith (Elsevier, 2016)
A tunable single-wavelength of an erbium-doped fiber ring laser is proposed and demonstrated. The laser integrates a tapered in-line Mach-Zehnder interferometer (IMZI) in its ring loop as an intracavity filter. The light spectrum is adjusted by changing an axial strain of the interferometer in a 60 μm range. As a result, a total tuning range of 6.19 nm that covers the wavelength from 1552.94 nm to 1559.13 nm is observed, and the sensitivity of 103.5 pm/μm is recorded. This high sensitivity lasing behavior is useful for high selectivity and fine tuning for narrow wavelength applications.